Digital technologies, online learning and lesson study. Issue 2 (29th April 2021) - Huang, Rongjin; Helgevold, Nina; Lang, Jean
Abstract : Purpose: Finding ways in which technology can be used to modify, strengthen, scale up and sustain lesson study (LS) is an emerging field of research. It has become even more important due to a pandemic leading to teacher and student learning being delivered online. The purpose of this paper is to present research findings about experiences of online LS and identify issues for further research. Design/methodology/approach: A systematic search of articles from 2010 to 2020 identified 13 relevant papers, and through analysis, some major themes were identified. All papers in the special issue were synthesized from the lens of the identified themes; finally, further directions are discussed. Findings: In general, various online LS models were found to have features that resulted in positive effects on teaching and learning, but, whilst several characteristics of effective online learning were identified, some studies also highlighted issues. Research limitations/implications: There is a need for larger scale projects over an extended period to assess the effectiveness of online LS. Future research focused on carrying out learning study online as well as consideration of equity issues associated with online LS are also suggested. Originality/value: The studies presented in this issue address the opportunities and challenges of conducting online LS during a pandemic and beyond. Together, the literature review and contributory papers provide an international perspective of using online LS and identify important issues for further research.